NTRK1-fusion as an acquired resistance mechanism in EGFRex19 mutated NSCLC: a case report - Li, Jielin; Shi, Yunyun; Zheng, Mengge; Yang, Chenkang; Gao, Hong; Li, Xiaoling (Frontiers in Pharmacology, 2025)
IntroductionA 73-year-old Chinese woman with no smoking history was diagnosed with stage IV adenocarcinoma of the lung in August 2020, presenting with left chest pain and multiple lung lesions.Patient concernsThe patient experienced chest pain for 2 months before diagnosis. Initial CT scans revealed multiple lung nodules, enlarged lymph nodes, and pleural effusion.DiagnosisThe diagnosis was confirmed as advanced NSCLC the left upper lobe of the lung with specific genetic alterations, including EGFR 19del, EGFR amplification, and TPR-NTRK1 fusion, through molecular testing.InterventionsPrior treatments included the first-line therapy gefitinib (250 mg/day) administered from September 2020 to June 2021, targeting the EGFR 19del mutation, achieving a partial response (PR). The second-line therapy osimertinib (80 mg/day) was administered from July 2021 to January 2022, targeting EGFR 19del and T790M mutations, with a progression-free survival (PFS) of approximately 7 months. The third-line therapy almonertinib, another third-generation EGFR-TKI, was administered from January 2022 to March 2022, but the response was poor, leading to further progression. After identifying NTRK fusion and EGFR amplification, the patient was administered larotrectinib as third-line treatment. Prior treatments included targeted therapies and chemotherapy.OutcomesDespite multiple lines of targeted therapy, the patient experienced rapid disease progression at several points, highlighting the challenges in managing NSCLC with complex genetic alterations.ConclusionThis case underscores the importance of ongoing molecular testing and the potential need for combination therapies in managing advanced NSCLC with resistance to multiple targeted treatments. The current treatment with camrelizumab combined with chemotherapy shows promise, but further monitoring is necessary.